Chemical Pretreatment Of Rubber Wood For Enzymatic Saccharification In Bioethanol Production - Alhassan, Alhassan Muhammad (2010)

(untitled)
The potentials of rubber wood to serve as raw material for bioethanol production was studied. The objective of this study was to investigate the effectiveness of sulphuric acid, nitric acid, sodium hydroxide and combinatorial nitric acid and sodium hydroxide pretreatments for conversion of rubber wood to ethanol. Sulfuric acid, nitric acid and sodium hydroxide, at concentrations of 1, 2 and 3% (w/v) were used to treat rubber wood sawdust samples at liquor to wood ratio of 1:6. Treatment temperatures of 80ºC and 100ºC were investigated for residence times of 30, 60, and 90 minutes. The combinatorial nitric acid and sodium hydroxide pretreatment was performed using nitric acid first followed by sodium hydroxide. Rubber wood sawdust was treated with dilute nitric acid (4,5 and 6%w/v) at temperatures of 90 or 100ºC for 30, 45 and 60 minutes followed by dilute sodium hydroxide (0.5, 0.75 and 1%), at 90ºC for 30 min. Lignin and carbohydrate, analyses were performed on the pretreated woods. The cellulose in the pretreated woods were then hydrolyzed using cellulases from Trichoderma reesei and β-glucosidase at 50ºC for 72 hrs and the released sugars were converted to ethanol by fermentation using yeast (Saccharomyces cerevisiae D5A strain). The results showed that time, temperature and concentration were all significant (p≤0.05) factors in lignin and hemicellulose reduction. Sulfuric acid pretreatment resulted in small lignin and hemicellulose reduction of 10.9% and 29.4% respectively, and glucose yield of 22.5% during enzymatic hydrolysis. Sodium hydroxide pretreatment resulted in higher, lignin and hemicellulose reduction of 51.0% and 30.1% respectively, and a glucose yield of 38.0%. Nitric acid pretreatment resulted in lignin and hemicellulose reduction of 30.6% and 64.9% respectively, and a glucose yield of 46.1%. Combinatorial nitric acid and sodium hydroxide pretreatment removes almost all the lignin and hemicellulose which resulted in isolated cellulose (95.8%) and a maximum glucose yield of 99.5%. The ethanol yield obtained after fermentation was 89.5% which is equivalent to 182.16g of ethanol per kg of rubber wood. The results obtained demonstrate that combinatorial nitric acid and sodium hydroxide pretreatment is an effective method for improving the enzymatic hydrolysis of rubber wood at moderate reaction condition and it is better than, sulphuric acid, sodium hydroxide or nitric acid pretreatment. The results also demonstrate that rubber wood is a potential raw material for bioethanol production.